STRENGTHENING BUREAUCRATIC REFORM IN THE BANDUNG CITY GOVERNMENT FROM THE PERSPECTIVE OF VISIONARY LEADERSHIP:: Study on Personnel and Resource Development Agency 2018-2023 - Haris Suddin Hakiki; Utang Suwaryo; Rahman Mulyawan (DIA: Jurnal Administrasi Publik, 2025)
Bureaucratic Reform is one of the important aspects in providing quality services. The purpose of bureaucratic reform is to have an impact on reducing the practice of corruption, collusion and nepotism, positive attitudes and moral values in people so that it has a positive impact on society and the surrounding environment. One factor that plays an important role in creating effective bureaucratic reform is visionary leadership. This research uses a qualitative approach using descriptive methods to gain an in-depth understanding of the visionary leadership of the Head of the Human Resources Staffing and Development Agency. The sources of information in this research are BKPSDM employees of Bandung City and the community. Information collection was done through interviews, observation and documentation. The results of this study indicate that the visionary leadership carried out by the head of BKPSDM Bandung City is running well. The head of BKPSDM Bandung City has the characteristics of a visionary leader in managing his organization. These steps include the establishment of the vision and mission of Bandung City which is the basis for the preparation of goals, objectives, strategies, programs, activities and sub-activities of BKPSDM. The vision and mission of Bandung City are outlined in a strategic plan that is prepared and submitted to all BKPSDM officials